Analysts earnings forecasts and tax avoidance strategies - Braga, Renata Nogueira (2023)
I examine the effects of analysts earnings forecasts on firms tax avoidance strategies. The firms engagement in conforming or non-conforming tax avoidance impacts their net income in opposing directions. While engagement in conforming tax avoidance reduces firms net income, engagement in non-conforming tax avoidance increases it. Therefore, engagement in different tax avoidance strategies brings the reported earnings closer to or further from the analysts forecasted earnings. I hypothesize and find that firms engage in more conforming tax avoidance activities as the reported earnings per share are further from the analysts consensus earnings forecast. I also test the effects of analysts earnings forecasts on conforming tax avoidance separately for firms with positive and negative earnings surprises and find that my main result persists in both groups of firms. My main result also persists in firms with lower or higher analyst coverage. I hypothesize that firms engage in more non-conforming tax avoidance activities as the reported earnings per share are closer to the analysts consensus earnings forecast. I find that for firms with negative earnings surprises, firms that report earnings per share closer to the analysts consensus earnings forecast engage in more non-conforming tax avoidance, consistent with my hypothesis. For firms with positive earnings surprises, I find that firms that report earnings per share closer to the analysts consensus earnings forecast engage in less non-conforming tax avoidance, inconsistent with my hypothesis. These findings indicate that firms that easily meet the analysts earnings forecasts engage complementarily in both conforming and non-conforming tax avoidance. The association between non-conforming tax avoidance and absolute earnings surprise persists in firms with lower analyst coverage but not in firms with higher analyst coverage. My main result persists in firms with lower analyst coverage but not in firms with higher analyst coverage. To test my hypotheses, I use a sample of profitable U.S. public firms with analysts coverage from 1994 through 2016, a period between two corporate tax reforms. My study contributes to broadening the understanding of the under-sheltering puzzle by knowing the extent to which analysts consensus earnings forecasts impact the constraint of non-conforming tax avoidance and/or the adoption of conforming tax avoidance.